Measuring and monitoring operational availability of rail infrastructure. (July 2016) - Stenström, Christer; Parida, Aditya; Kumar, Uday
In reliability and maintenance engineering, availability can be described as the ability of an item to be in a state to perform a required function at a given time. Availability is commonly given as a measure between zero and one, where one means the probability of an item to be available for use at a given time is 100%. Availability is measured in many areas, such as electronics, information technologies, military equipment, electrical grids and the industry. Various indicators related to availability of railways have been examined by academia and industry. However, there is some ambiguity about how to define and measure the availability of rail infrastructure, given railways' semi-continuous operation, besides data quality issues. This article considers the application of common definitions of availability to rail infrastructure. It includes a case study comparing various approaches for measuring availability. The case study ends with a section on how availability as a function of train frequency and maintenance time can be simulated. The results show rail infrastructure availability correlates well with train delay, but this depends on how infrastructure failure data and outliers are treated.